Adopsi dan Inovasi Pendidikan - Sukatin, Sukatin; Afrini, Novia; Marselinda, Vina; Widyatama, Ikhsan; Sakdiah, Nur (Medan Resource Center, 2023)
An innovation's utility hinges on its adoption. According to Mardikanto (1993), adoption entails a behavioral shift encompassing cognitive, affective, and psychomotor domains following the delivery of a message by an instructor to the target audience. Fundamentally, adoption entails a process that traverses various stages before a community decides to embrace or discard an innovation. The stages in the adoption of biopesticides commence with the introduction phase, wherein individuals become aware of the innovation's existence. Subsequently, the persuasion stage ensues, during which individuals cultivate attitudes towards the innovation. The subsequent stage involves the decision to embrace or reject the innovation. Lastly, the process culminates in the confirmation stage, wherein individuals seek reinforcement for their decision to either proceed with the innovation's implementation or forgo it altogether.